Development of Puzzle Games to Foster Basic Mathematical Skills in Early Childhood - Verdy Bayu Winarso; Rafika Kusumandari (FKIP, Universitas Palangka Raya, 2026)
Basic mathematical skills in preschool children often face developmental challenges due to the lack of interactive and engaging learning resources in kindergartens. This community service activity aims to implement and test the effectiveness of a puzzle game-based educational media application in enhancing children's learning interest and analytical thinking skills. The developed puzzle game application integrates three types of educational games: selecting animals according to their habitat in the first game, matching geometric shapes into empty spaces in the second game, and counting the number of animals that appear in the third game. The method applied follows the Research and Development (R&D) approach to create a valid and practical product for partners. Field data analysis shows that validation by media experts recorded an average score of 95.1%, falling into the highly valid category. On the other hand, the validation of the student learning interest instrument reached a score of 95.8%, indicating a high level of relevance. The tangible results of using this media demonstrate a clear and significant increase in children's positive responses and learning enthusiasm during basic mathematics sessions. Thus, this puzzle game-based learning is proven effective as an alternative method to enhance mathematical thinking skills in preschool children.